Between Conflict and Co-Operation: Globalisation and the Future of International Relations - Attuquayefio, P. (My University, 2008)
In the past decade or two, the concept of Globalisation has received extensive hype in academic and developmental dialogue. While an overwhelming number of such discussions cite globalisation as involving the removal of some form of boundary and other cooperative phenomena, a critical examination of all the processes globalisation stimulates reveals that it has the potential of generating or sustaining conflict in international relations. This article examines the co-operative aspects of globalisation. It also explores some positions that point to the possibility of increased conflict in international relations. In looking at the prospects for co-operation this article discusses Immanuel Kant’s tripod of courses namely-democracy, membership in international institutions and economic interdependence.it also presents the territorial argument and the neo-liberal perspective of increase in international co-operation due to realisation of common interests and the gradual elimination of cultural barriers . As regards the prospects for conflicts in international relations, the article discusses the challenges arising from the globalisation of political values as well as culture, threats from the internet, challenges of social injustice and international terrorism. On the basis of the discussion the article concludes that the future of international relations insofar as globalisation is concerned, lies between conflict and co-operation. Consequently, it recommends that the apparent mass delusion about the absolutely positive aspects of globalisation must be replaced by conscious efforts by all stakeholders in international relations to ensure that the factors that generate conflict are acknowledged and efforts made at addressing them, while those that enhance co-operation are encouraged.